(untitled) (Jurnal Ilmu dan Teknologi Kelautan Tropis, 2024)
The problem of plastic waste in Indonesia is considered an emergency status, following research results that place Indonesia as the largest contributor to marine plastic waste in the world after China. The lack of information about marine pollution on the coast is a problem in its handling, especially in Brebes Regency, Central Java. This study aims to identify the types of marine debris and estimate their composition and distribution on the coast of Randusanga Brebes Beach. Marine debris sampling was carried out using the quadrant transect observation method which was carried out three times with a total of 15 transects in August-October 2021. Data was analyzed using Graphical Data Analysis (GDA) approach. Of the various types of waste found, plastic waste was the most dominant waste found with 869 items, followed by 190 items of plastic foam, 57 items of paper and cardboard, 48 items of wood, 36 items of rubber, 34 items of other materials, 22 items of metal, 8 items of cloth, as well as glass or ceramic as much as 4 grains. Based on size, macro-sized waste is the most commonly found waste. The total amount of macro debris found at the study site was 1,222 items, while the meso debris was 66 items. Percentage composition of tents: plastic bags (71%), plastic foam (15%), fabrics (4%), glass and ceramics (0%), metal (0%), paper and cardboard (4%), rubber (0%) , wood (2%), other materials (4%). Types of plastic waste based on the Resin Indetification Code (RIC) consist of polypropylane (PP), low density polyethylene (LDPE), others (OT), polystyrene (PS), high density polyethylene (HDPE), polyethylene terephthalate (PET/PETE) waste. The high abundance of marine debris every month is closely related to the lack of public awareness of the sustainability of the surrounding ecosystem and the lack of awareness of the implementation of Government Regulations regarding the handling of applicable waste.